5-Aminosalicylic acid downregulates the growth and virulence of Escherichia coli associated with IBD and colorectal cancer, and upregulates host anti-inflammatory activity. (November 2018) - Zhang, Shiying; Fu, Jing; Dogan, Belgin; Scherl, Ellen; Simpson, Kenneth
Abstract 5-aminosalicylate (5-ASA) is widely prescribed for the treatment of inflammatory bowel disease (IBD) and prevention of inflammation-associated colorectal cancer (CRC). Its clinical effect is widely attributed to modulation of host inflammatory responses. However, the recent association of intestinal dysbiosis and selective enrichment inEscherichia coli in patients with IBD and CRC raises the possibility that 5-ASA might also affect the enteric microflora. The aim of this study was to investigate the effect of 5-ASA on the growth and virulence ofE. coli associated with IBD and CRC, and its impact on host cell inflammatory responses. Our results show that 5-ASA inhibitedE. coli growth in a dose-dependent manner and downregulated the expression of bacterial virulence genes associated with IBD(fliC, fimH, ompC, yfgL, nlpL, lpfA, htrA, dsbA, fyuA, andchuA) and CRC (pks). 5-ASA inhibitedE .coli motility (30–70%), epithelial adherence and invasion, and IL-8 secretion (p < 0.05). 5-ASA reducedE .coli survival in J774A.1 macrophages by 20 to 50% (p < 0.01) and TNF-α secretion by infected macrophages up to 30% (p < 0.05). In addition, 5-ASA reduced DNA damage in epithelial cells (Caco-2) induced bypks -positiveE. coli . Our results reveal a multifaceted and previously unrecognized effect of 5-ASA on the growth and virulence of IBD- and CRC-associatedE .coli, in addition to its inhibitory effect on host cell inflammatory responses. These results suggest that 5-ASA may abrogate the proinflammatory and oncogenic effects ofE .coli in patients with IBD and CRC.